ASSESSMENT AND EDUCATIONAL INTERVENTIONS IN INHALATION TECHNIQUE AMONG ASTHMA AND COPD PATIENTS AT A TERTIARY CARE HOSPITAL IN ERODE (Tamilnadu- India): Pharmaceutical Science-Pharmacy Practice - VIDHYA PV; JEENA S; SAMBATHKUMAR R; VENKATESWARAMURTHY N (International Journal of Life Science and Pharma Research, 2019)
The aim of this research was to assess the quality of inhalation technique in patients and to determine the effect of a single intervention by clinical pharmacist to improve knowledge of patient regarding the use of inhalers among asthma and Chronic Obstructive Pulmonary Disease (COPD) patients. A total of 223 patients with asthma or COPD using inhaler medication were randomly selected. During the first appointment, patients were interviewed and their inhalation technique was assessed with checklists. Errors were recorded and counselling with practical demonstration of proper inhalation technique was given. After 3 days, inhalation technique by the patients was reassessed and recorded using checklist. Pre and post comparison were performed to assess the impact of education by pharmacist about inhalation technique among asthma and COPD patients. All the patients committed at least single one error in their inhalation technique. There was a significant reduction in the number of patients who committed error in the first appointment to second appointment. Out of 223 patients, 162 patients (72.6%) committed error in the step 5 (exhale normally) in the first appointment. This number dropped to 21 (9.4%) in the second appointment after counselling with practical demonstration (P < 0.015). Correct inhalation technique is essential for effective drug delivery in COPD and asthma. The inhalation technique of asthma and COPD in patients is poor. Pharmacists can play a pivotal role in improving health outcomes for patients with asthma and COPD by providing knowledge on how to use their inhaler devices properly.